Protective Effect of Icariin on the Development of Preimplantation Mouse Embryos against Hydrogen Peroxide-Induced Oxidative Injury. (7th June 2017) - Ye, Rong; Xu, Songhua; Liu, Yue; Pang, Lili; Lian, Xiuli; Zhong, Yuhuan; Su, Yang; Wang, Shie
Abstract : During in vitro cultivation of preimplantation embryos, the balance between ROS production and clearance is disturbed and may lead to incompetent embryos, which might be a main reason of IVF-ET failure. Icariin (ICA) is reported to be active in clearing ROS. The present study aimed to investigate whether ICA could reverse H2 O2 pretreatment-induced mouse preimplantation embryo development arrest and, furthermore, to study the underlying mechanisms by detecting ROS levels, mitochondrial membrane potential (Δ Ψ m), and zygotic gene expression. The results showed that, after pretreating mouse 1-cell embryos with 40  μ M or 60  μ M H2 O2 for 30 min, the developmental rate of each stage embryos decreased obviously. And by adding 40  μ M ICA, the developmental arrest of 60  μ M H2 O2 pretreated preimplantation embryos was significantly reversed. Immunostaining results showed that, comparing with the control group, ROS levels of H2 O2 pretreated 1-cell embryos were elevated and Δ Ψ m levels decreased. By adding ICA, the ROS levels of H2 O2 pretreated 1-cell embryos were decreased and Δ Ψ m levels were elevated. Furthermore, RT-qPCR results showed that the addition of ICA reversed the H2 O2 -induced downregulation of eIF-1A mRNA expression levels. These results indicate that ICA, when used in appropriate concentration, could decrease ROS levels, increase Δ Ψ m levels, and modulate the expression of zygotic gene activation (ZGA) marker gene eIF-1A, and thus promote the development of H2 O2 -pretreated mouse preimplantation embryos.